103k views
3 votes
Solve =14+3 l = 14 j + 3 k for k. Select one: a. =+143 k = l + 14 j 3 b. =−143 k = l − 14 j 3 c. =3+14 k = l 3 + 14 j d. =3−14

User Pranvera
by
5.9k points

2 Answers

7 votes

Answer:

Which expression is equivalent to ‐10

k

10

?

Explanation:

User Birgire
by
6.5k points
1 vote

Answer:

k= l/3 - 14/3j

Explanation:

l = 14j + 3k

Solve for k

l = 14j + 3k

Subtract 14j from both sides

l - 14j =14j + 3k - 14j

l - 14j = 3k

Divide both sides by 3

l - 14j / 3=3k / 3

k= l/3 - 14/3j

Or

1/3(l - 14j) = k

User Suntoch
by
5.6k points